Specific Macro Factors Affecting Economic Growth During the COVID-19 Pandemic : Evidence from EAGLEs - Thach, Nguyen Ngoc; Linh, Nguyen Tran Xuan; Hac, Le Dinh; Ngoc, Lam Thai Bao; Hai, Do Huu (Indian Journal of Finance, 2022)
The study was conducted to assess the impact of macro factors on economic growth in emerging and growth-leading economies (EAGLEs) during the COVID-19 pandemic. The study applied a Bayesian simulation method, and the empirical results exhibited an ambiguous impact of trade openness and the number of internet users on economic growth in these countries during the COVID-19 outbreak. Besides, in response to the economic downturn caused by the COVID-19 pandemic, countries have loosened monetary and fiscal policies simultaneously. However, policy rate reduction was found to be less efficient in the countries previously applying low-interest rates. The evidence showed that reasonable pandemic control measures formed a basis for fastening economic recovery.